Quo vadis German Housing Policy? - Norbert Hiller; Daniel Schultewolter (Wirtschaftsdienst, 2014)
The massive increase of real estate prices in some regions of Germany is a direct consequence of the ongoing financial and debt crisis. Low interest rates and high inflation expectations increase the demand for real estate. In addition to a potential price bubble risk, social problems arouse more and more public interest. Currently, many tenants are facing significant rent increases. Thus, the shortage of housing dominates current housing policy discussions. The so-called “package for affordable building and living” includes stricter rent controls and other economic policy interventions which aim to ease the situation in the real estate market, but the interventions have the opposite effect. – – In den Koalitionsverhandlungen wurde ein ,,Paket für bezahlbares Bauen und Wohnen“ vereinbart. Das Paket enthält unter anderem eine Mietpreisbremse, deren Wirkung die Autoren insbesondere auf längere Sicht kritisch sehen. Sie fürchten, dass dadurch weniger Wohnungen angeboten werden und ein Schwarzmarkt den Preismechanismus, der Anbieter und Nachfrager zusammenbringt, ablöst. Alle Beteiligten müssten dann Nachteile erleiden.
Additional information: Es handelt sich um eine englische Übersetzung des Originals.
Keywords: R31; R32; R38; 330; Housing Policy; Rent Control; Regulatory Policies; Wohnungspolitik; Preisregulierung; Regulierung